Performativität in Sprache und Recht - Bülow, Lars; Bung, Jochen; Harnisch, Rüdiger; Wernsmann, Rainer (Sprache und Wissen, 2016)
"This compendium offers access to readers interested in the humanities and in social, cultural, and legal studies to a broad and multifaceted exploration of linguistic practices in the legal sciences. A range of scholars from the fields of linguistics and the legal sciences focus on specific performative aspects of the connections between language and the law."--